Manado children's choice echo trumpet (review aspects of establishment and development) - Meyny S. C. Kaunang; Lucylle Takalumang (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The purpose of this study was to examine and describe the children's choir of Gema Trumpets, review and how the process of making the Children's Choir of Gema Sangkakala Manado, How is the process of fostering the Children's Choir of Gema Sangkakala Manado, What are the factors that hinder the process? Ordering and coaching the Manado Echo Sangkakala Children's Choir, and What efforts have been made to overcome the obstacles to ordering and coaching the Echo Trumpets Children's Choir. The research method used in this study is qualitative. Data technique is done by observation, interview, documentation study. coaching, namely: After analyzing the data, it was concluded that The reservation of the Gema Sangkakala Manado children's choir was a response to the public's interest, especially choir observers to accommodate the potential of children who have interests and talents in senior vocals, especially in the choir. , as part of the development of the organization (Studio) to contribute to fostering children's attitudes and behavior through the chorus, to motivate in general in cultivating and attracting children's interest in their love of good singing skills through praise, Age limits and parents, as well as children in the Choir by showing the impact of fostering children on a changing process, the management of the process always requires substantial funds by relying only on non-permanent donors, and Efforts which were carried out to overcome various obstacles in the choir, among others, recruiting members followed by b . interviews both for children and parents, involving parents in the preparation of activity programs that are tailored to the child's schedule, fundraising is carried out at any time including scheduling concert programs that are held regularly.